2008
DOI: 10.1111/j.1744-618x.2008.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Inhibit the Use of Nursing Language

Abstract: Electronic records may contribute to the implementation of the nursing process, particularly if the identified signs and symptoms are documented and then linked to nursing diagnoses and interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 14 publications
4
24
0
5
Order By: Relevance
“…Several investigators found that nurses might not be willing to use ND because of lack of time, lack of education related to ND (Paganin, Moraes, Pokorski, & Rabelo, 2008;Whitley & Gulanick, 1996), and negative attitudes toward ND (da Cruz Dde, Hayashi, Oliva, & Correa, 2006;Lunney & Krenz, 1992;Paans et al, 2011). However, when nurses' attitudes toward ND are positive, they use ND more effectively (Oliva, de Almeida Lopes, Volpato, & Hayashi, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…Several investigators found that nurses might not be willing to use ND because of lack of time, lack of education related to ND (Paganin, Moraes, Pokorski, & Rabelo, 2008;Whitley & Gulanick, 1996), and negative attitudes toward ND (da Cruz Dde, Hayashi, Oliva, & Correa, 2006;Lunney & Krenz, 1992;Paans et al, 2011). However, when nurses' attitudes toward ND are positive, they use ND more effectively (Oliva, de Almeida Lopes, Volpato, & Hayashi, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…Em estudo prévio realizado na mesma instituição, foram identificados os fatores que mais interferiam na implementação da etapa do DE, como plantões agitados, o envolvimento com tarefas administrativas e dificuldades de ordem práti-ca (18) . Relacionada a este último item, a discussão de casos clínicos em equipes multiprofissionais, que cada vez mais tem sido instituída em terapia intensiva, em prol de uma assistência mais qualificada, foi incentivada entre enfermeiros, com o objetivo de instrumentalizá-los para a elaboração dos DE.…”
Section: Métodosunclassified
“…Furthermore, results of a study conducted in the same institution aiming to evaluate the difficulties, in the view of nurses, to establish a nursing diagnosis in an ICU, revealed that the severity of a patients' condition, the number of patients per nurse and administrative tasks, were factors related to this assignment (12) . In addition to the risks factors and DC for the most prevailing nursing diagnoses, the treatments prescribed were listed through cross-mapping.…”
Section: Methodsmentioning
confidence: 99%